Sulforaphane increases drug-mediated cytotoxicity toward cancer stem-like cells of pancreas and prostate - Kallifatidis, Georgios; Labsch, Sabrina Daniela; Rausch, Vanessa; Mattern, Jürgen; Gladkich, Jury; Moldenhauer, Gerhard; Büchler, Markus W.; Salnikov, Alexey V.; Herr, Ingrid (Molecular therapy, 2011)
Despite intense efforts to develop treatments against pancreatic cancer, agents that cure this highly resistant and metastasizing disease are not available. Considerable attention has focused on broccoli compound sulforaphane (SF), which is suggested as combination therapy for targeting of pancreatic cancer stem cells (CSCs). However, there are concerns that antioxidative properties of SF may interfere with cytotoxic drugs - as suggested, e.g., for vitamins. Therefore we investigated a combination therapy using established pancreatic CSCs. Although cisplatin (CIS), gemcitabine (GEM), doxorubicin, 5-flurouracil, or SF effectively induced apoptosis and prevented viability, combination of a drug with SF increased toxicity. Similarly, SF potentiated the drug effect in established prostate CSCs revealing that SF enhances drug cytotoxicity also in other tumor entities. Most importantly, combined treatment intensified inhibition of clonogenicity and spheroid formation and aldehyde dehydrogenase 1 (ALDH1) activity along with Notch-1 and c-Rel expression indicating that CSC characteristics are targeted. In vivo, combination treatment was most effective and totally abolished growth of CSC xenografts and tumor-initiating potential. No pronounced side effects were observed in normal cells or mice. Our data suggest that SF increases the effectiveness of various cytotoxic drugs against CSCs without inducing additional toxicity in mice.
Published online12 October 2010
Gesehen am 07.07.2022